A Spy's guide to strategy - Braddock, John. (2017)
When you?re a spy, life is complex. There are long games and short games and games that don?t matter. There are enemies, allies and allies who become enemies. There?s ambiguity, lying and betrayal. It?s on you to make sense of it. Just you.
Keywords: Strategy